An Analysis of Factors that Affectefl Students' Writing Skill - M. Kemalsyah; Moh. Solehuddin; Ahmad Hariyadi; Jenuri Jenuri; Dina Mayadiana Suwarma (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
Writing skills are a specific perspective that allows writers to put their thoughts into words. Students mentally connect with words and messages through writing skills. Writing, on the other hand, is a difficult skill to master. It requires the ability to combine words and sentences. The researcher used qualitative research. Qualitative research methods focus on in-depth understanding, interpretation, and disclosure of the meaning of the data collected. The type of research used by the researcher is a case study. A case study is used because the researcher can understand the context, process, and complexity of the phenomenon under study. This type of research allows the researcher to explore perspectives, experiences, and meanings in the data collected related to An Analysis of Factors that Affectefl Studentsaffect students research results can provide deep, contextual, and detailed insights into the case under study, which can be used to inform policies, practices, or further theoretical development. The subjects in this study are English Education Students at a University in Jakarta, Indonesia. Based on the findings and discussion, it can be concluded that students who are less motivated, less confident, and do not want to practice writing are due to several interrelated factors. These factors are a misunderstanding of writing, lack of experience, and negative self-perception. Misunderstanding writing can make students feel that writing is difficult and boring. Lack of experience can lead students not to have the skills they need to write well. Negative self-perception can lead students to feel that they are not good writers and will never be able to improve their skills. Therefore, to improve students' motivation, confidence, and interest in writing, efforts must be made to address these factors. Teachers and students must collaborate to develop effective and efficient writing learning strategies.